ANALISIS SWOT KONVERSI KOPERASI KONVENSIONAL KE KOPERASI SYARIAH - Lubis, Fauzi Arif (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to analyze the SWOT conversion of Conventional Cooperatives to Sharia Cooperatives at KPRI Sejahtera Bersama. The method used in this research is descriptive qualitative method. The data was obtained through a consultant with management and members of KPRI Sejahtera Bersama as well as collaborative studies related to cooperative activities. The results of the SWOT analysis show that converting to sharia cooperatives has high profit potential, but also faces several obstacles such as limited costs and human resources. The calculation results of the Internal Strategic Factors Analysis Summary (IFAS) show that the strengths outweigh the weaknesses. The calculation results of the External Strategic Factors Analysis Summary (EFAS) show that the opportunities outweigh the threats. This research is expected to contribute to the development of Islamic cooperatives in Indonesia